Topical administration of a suppressor of cytokine signaling-1 (SOCS1) mimetic peptide inhibits ocular inflammation and mitigates ocular pathology during mouse uveitis. (August 2015) - He, Chang; Yu, Cheng-Rong; Sun, Lin; Mahdi, Rashid M.; Larkin, Joseph; Egwuagu, Charles E.
Abstract: Uveitis is a diverse group of potentially sight-threatening intraocular inflammatory diseases and pathology derives from sustained production of pro-inflammatory cytokines in the optical axis. Although topical or systemic steroids are effective therapies, their adverse effects preclude prolonged usage and are impetus for seeking alternative immunosuppressive agents, particularly for patients with refractory uveitis. In this study, we synthesized a 16 amino acid membrane-penetrating lipophilic suppressor of cytokine signaling 1 peptide (SOCS1-KIR) that inhibits JAK/STAT signaling pathways and show that it suppresses and ameliorates experimental autoimmune uveitis (EAU), the mouse model of human uveitis. Fundus images, histological and optical coherence tomography analysis of eyes showed significant suppression of clinical disease, with average clinical score of 0.5 compared to 2.0 observed in control mice treated with scrambled peptide. We further show that SOCS1-KIR conferred protection from ocular pathology by inhibiting the expansion of pathogenic Th17 cells and inhibiting trafficking of inflammatory cells into the neuroretina during EAU. Dark-adapted scotopic and photopic electroretinograms further reveal that SOCS1-KIR prevented decrement of retinal function, underscoring potential neuroprotective effects of SOCS1-KIR in uveitis. Importantly, SOCS1-KIR is non-toxic, suggesting that topical administration of SOCS1-Mimetics can be exploited as a non-invasive treatment for uveitis and for limiting cytokine-mediated pathology in other ocular inflammatory diseases including scleritis. Highlights: Topical SOCS1-KIR inhibits inflammation and confers protection from severe uveitis. SOCS1-KIR inhibits Th17 expansion and trafficking of inflammatory cells into retina. SOCS1-KIR is neuroprotective and prevents decrement of retinal function in uveitis. SOCS1-KIR is a non-toxic, non-invasive therapy with no effects on systemic immunity. SOCS1-KIR may also have utility in treatment of other ocular inflammatory diseases.